2013
DOI: 10.1016/j.marchem.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dicarboxylic acids, ketocarboxylic acids and glyoxal in the marine aerosols collected during a round-the-world cruise

Abstract: This study investigated spatial distributions of water-soluble dicarboxylic acids and related compounds in the marine aerosols collected at low-to mid-latitudes in the NorthernHemisphere for a better understanding of the photochemical aging of organic aerosols during long-range transport. Their molecular distributions were characterized by the predominance of oxalic acid (C 2 ) followed by malonic (C 3 ) and succinic (C 4 ) acids, except for one sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
119
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 81 publications
(100 reference statements)
4
119
3
Order By: Relevance
“…A recent study of marine aerosol from around the globe found that DCA contribute on average ∼ 15 % to total marine organic aerosol (OA) mass (Fu et al, 2013;Myriokefalitakis et al, 2011). DCA are commonly associated with aqueous processing of water soluble organics Tan et al, 2010) and hence readily affect aerosol-water interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of marine aerosol from around the globe found that DCA contribute on average ∼ 15 % to total marine organic aerosol (OA) mass (Fu et al, 2013;Myriokefalitakis et al, 2011). DCA are commonly associated with aqueous processing of water soluble organics Tan et al, 2010) and hence readily affect aerosol-water interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Oxalic acid (OxA) is typically the dominant DCA found in aerosol (Neusüss et al, 2000). It was shown to contribute more than 50 % on average of the total mass of marine DCA, and mineral dust is often enriched in OxA (Sullivan et al, 2009;Fu et al, 2013). High oxidation states and the ability to strongly interact with inorganic compounds (especially crustal/marine salts) make the effects of DCA on aerosol composition and physical properties unique and complex.…”
Section: Introductionmentioning
confidence: 99%
“…The C3/ C4 ratios in the marine aerosols collected at low-to mid-latitudes in the Northern Hemisphere vary between 0.9 and 5.8 with an average of 2.3, which were about three times higher than those found in urban aerosol (Fu et al, 2013). These values suggested that C 3 -malonic acid is photochemically produced during long range transport from continents to the marine atmosphere (Fu et al, 2013). The mean C 3 /C 4 ratio calculated in the 2014/2015 Antarctic samples ranged between 0.8 and 2.3 with an average value of 1.45, suggesting that aerosol contained these species underwent long range transport processes, where photochemical degradation occurred.…”
Section: Carboxylic Acids (Ca) In Pm 10mentioning
confidence: 76%
“…C 2 -oxalic acid is an end-product of various oxidation/decomposition reactions in the atmosphere (Kawamura and Sakaguchi, 1999), whereas the presence of long chain CA suggests incomplete photochemical degradation of alkenes in the atmosphere. The C 3 -malonic/C 4 -succinic ratio can be used as an indicator of enhanced photochemical production of diacids (Kawamura and Ikushima, 1993), as C 4 -succinic acid can be degraded to C 3 -malonic acid by decarboxylation reactions activated by OH radicals (Fu et al, 2013). The C3/ C4 ratios in the marine aerosols collected at low-to mid-latitudes in the Northern Hemisphere vary between 0.9 and 5.8 with an average of 2.3, which were about three times higher than those found in urban aerosol (Fu et al, 2013).…”
Section: Carboxylic Acids (Ca) In Pm 10mentioning
confidence: 99%
See 1 more Smart Citation